Tabata training in perspective - Tabata, I. (Applied Physiology, Nutrition, and Metabolism, 2025)
Originally developed as a specific form of exhaustive intermittent training involving 6-8 × 20 s of supramaximal-intensity cycling exercises with 10 s of recovery for athletes, Tabata training has become universally recognized around the world. The purpose of this review article is to provide a perspective on Tabata training and discuss how this popular style of intermittent training has evolved and been applied over the last ~30 years. The article will review the original motivation behind Tabata training with relevance to concepts such as maximal accumulated oxygen deficit and maximal oxygen uptake (VO2max) and discuss how Tabata training has been adapted to involve sport-specific training and cross training. Studies of Tabata training on physiological responses and adaptations in muscle, blood vessels, bone, and brain across different populations will be reviewed. Finally, research on how Tabata-style training was applied to counteract inactivity during the COVID19 pandemic will be discussed. Evolving from the study of athletes, Tabata training represents an example of how high-intensity intermittent/interval training can be adapted and applied in various settings to enhance performance and health.